Modulation of Cellular Redox Parameters for Improving Therapeutic Responses in Multiple Myeloma - Alessandro Allegra; Claudia Petrarca; Mario Di Gioacchino; Marco Casciaro; Caterina Musolino; Sebastiano Gangemi (MDPI AG, 2022)
Raised oxidative stress and abnormal redox status are typical features of multiple myeloma cells, and the identification of the intimate mechanisms that regulate the relationships between neoplastic cells and redox homeostasis may reveal possible new anti-myeloma therapeutic targets to increase the effectiveness of anti-myeloma drugs synergistically or to eradicate drug-resistant clones while reducing toxicity toward normal cells. An alteration of the oxidative state is not only responsible for the onset of multiple myeloma and its progression, but it also appears essential for the therapeutic response and for developing any chemoresistance. Our review aimed to evaluate the literature's current data on the effects of oxidative stress on the response to drugs generally employed in the therapy of multiple myeloma, such as proteasome inhibitors, immunomodulators, and autologous transplantation. In the second part of the review, we analyzed the possibility of using other substances, often of natural origin, to modulate the oxidative stress to interfere with the progression of myelomatous disease.